Penerapan Teams Game Tournament untuk Meningkatkan Motivasi Belajar pada Submateri Struktur dan Fungsi Reproduksi Manusia - Reza, Muhammad; Panjaitan, Ruqiah Ganda Putri; Ruslah, Ruslah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
This research aims to increase students' learning motivation on the sub-material of the structure and function of the human reproductive system, using the Teams Game Tournament learning model. This research is collaborative action research carried out at SMP Negeri 6 Pontianak from July to August 2023. The research was carried out in two learning cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The research subjects came from class IX F students with a total of 28 students consisting of 12 men and 16 women. The instruments used were learning implementation observation sheets and student learning motivation questionnaires. Data analysis uses descriptive statistical techniques. The learning process in cycle 1 was carried out with a percentage of 86% and increased in cycle 2 to 100% with very good criteria. The percentage value of student learning motivation in cycle 1 was 72.73%, and increased in cycle 2 to 80.20% with high criteria. Students with high learning motivation in cycle 1 were 55.85%, and increased in cycle 2 to 83.57%. It can be concluded that the application of the Teams Game Tournament model can increase student learning motivation in the sub-material of the structure and function of the human reproductive system.